Analysis of the frequency and spectrum of mutations recognised to cause familial hypercholesterolaemia in routine clinical practice in a UK specialist hospital lipid clinic - Futema, M; Whittall, R; Kiley, A; Steel, L; Cooper, J; Badmus, E; Leigh, SE; Karpe, F; Neil, H; Humphries, SE (2013)
Aim: To determine the frequency and spectrum of mutations causing Familial Hypercholesterolaemia (FH) in patients attending a single UK specialist hospital lipid clinic in Oxford and to identify characteristics contributing to a high mutation detection rate. Methods: 289 patients (272 probands) were screened sequentially over a 2-year period for mutations in LDLR, APOB and PCSK9 using standard molecular genetic techniques. The Simon Broome (SB) clinical diagnostic criteria were used to classify patients and a separate cohort of 409 FH patients was used for replication. Results: An FH-causing mutation was found in 101 unrelated patients (LDLR=54 different mutations, APOB p.(Arg3527Gln)=10, PCSK9 p.(Asp374Tyr)=0). In the 60 SB Definite FH patients the mutation detection rate was 73% while in the 142 with Possible FH the rate was significantly lower (27%, p<0.0001), but similar (14%, p=0.06) to the 70 in whom there was insufficient data to make a clinical diagnosis. The mutation detection rate varied significantly (p=9.83×10-5) by untreated total cholesterol (TC) levels (25% in those <8.1mmol/l and 74% in those >10.0mmol/l), and by triglyceride levels (20% in those >2.16mmol/l and 60% in those <1.0mmol/l (p=0.0005)), with both effects confirmed in the replication sample (p for trend=0.0001 and p=1.8×10-6 respectively). There was no difference in the specificity or sensitivity of the SB criteria versus the Dutch Lipid Clinic Network score in identifying mutation carriers (AROC respectively 0.73 and 0.72, p=0.68). Conclusions: In this genetically heterogeneous cohort of FH patients the mutation detection rate was significantly dependent on pre-treatment TC and triglyceride levels. © 2013 The Authors.